METHODS OF PRODUCT DISTRIBUTION OF ENTERPRISES ENGAGED IN FOREIGN ECONOMIC ACTIVITIES: ESSENCE AND FEATURES OF PLANNING - Билец, Леся; Чиркова, Юлия (SWorldJournal, 2020)
Today, sales activities are the key component of the competitiveness of almost every enterprise engaged in foreign economic activities. In modern economic conditions and the intensification of globalization, more and more attention is paid to the distrib